The Effect Of E-Wallet, a Hedonist Lifestyle with Self Control as an Intervening Variable on Consumptive Behavior - nikma yucha; Ria Angelina Nur Rohmah (Universitas Dinamika, 2023)
This study aims to prove and analyze the effect of e-wallet, a hedonist lifestyle with self-control as an intervening variable on Consumptive Behavior. This study uses quantitative methods, and data collection using questionnaires. The sample was selected using non-probability sampling with a total of 182 respondents. And data processing and analysis using path Analyzes. The results of this study can be concluded that E-wallet Variable has a positive and significant effect on self-control. Hedonic lifestyle variables have a positive and significant effect on self-control. The hedonic lifestyle has a positive and significant effect on consumer behavior. Self-control variable has a positive and significant effect on consumptive behavior. E-wallet variables have a positive and unsignificant effect on consumptive behavior through self-control. Hedonic lifestyle variable has a positive and unsignificant on consumptive behavior through self-control.